Sosialisasi Hukum Waris dan Pendampingan Pengelolaan Keuangan Desa di Desa Bening Kecamatan Gondang Kabupaten Mojokerto (Lembaga Pengembangan Kinerja Dosen, 2026)
Limited understanding of inheritance law and village financial management among village officials remains a significant issue that may trigger social conflict and weaken village governance effectiveness. This community service program aims to strengthen the capacity of village officials through inheritance law socialization and assistance in village financial management. The activity employed a descriptive method with a participatory approach. Implementation was carried out through structured socialization sessions, interactive discussions, and direct technical assistance adjusted to village administrative practices. Data collection techniques included observation, documentation, and pre-and post-activity evaluations to measure participants’ understanding. The results demonstrate an improvement in village officials’ knowledge of basic inheritance law principles and their awareness of transparent, accountable, and regulation-based village financial management. Furthermore, the program enhanced officials’ understanding of their strategic role in addressing community legal issues and supporting good village governance. Overall, this activity contributes to improving the professionalism and accountability of village administration in delivering community-oriented public services.